The Development of Ungauged-Catchment Integrated-Similarity Unit Hydrograph to Estimate Inflow of Wonogiri Reservoir - Santoso, Kurniawan Putra; Istiarto; Jayadi, Rachmad (Journal of the Civil Engineering Forum, 2023)
The Wonogiri Reservoir is a multipurpose reservoir at the Upper Bengawan Solo Watershed, primarily designed to serve as a flood control system. However, there is no accurate estimation of the inflow into the reservoir due to the limited availability of hydrological stations. Observations showed only four out of ten unit hydrographs of the Wonogiri Reservoir watershed. Therefore, this study was conducted to apply an integrated similarity-based approach for designing unit hydrographs in ungauged catchments. The process involved evaluating the integrated similarity between pairs of gauged-ungauged catchments using hydrologic and physical property parameters. This led to the selection of the donor or gauged catchment with the highest similarity score to develop the unit hydrograph for the ungauged catchments. The developed UHs were further applied to estimate the reservoir inflow for the December 25, 2007, flood event. The results showed that the computed peak discharge was 10.9% lower than a previous study. Subsequently, the HEC-HMS simulation model was used to project the updated design flood hydrographs to the reservoir. The design rainfall was derived from automatic rainfall recorder (ARR) and PERSIANN satellite-based data. The ARR data showed that the extreme rainfall duration was 5 hours while satellite data indicated 6 hours. The application of the ARR 5-hour duration to the updated flood hydrographs led to a peak discharge of 5123 m3 s-1, 7041 m3 s-1, and 10,370 m3 s-1 for the 60-year, 500-year, and PMF floods respectively in line with the flood design criteria of Wonogiri Reservoir. These estimates were observed to be significantly higher than the 1982 design floods which were 4000 m3 s-1, 5100 m3 s-1, and 9600 m3 s-1 respectively. This updated flood control design was important to renew the operation rule of the Wonogiri reservoir during flood periods.